Inhibiting ADORA1 enhances glioma apoptosis and increases its sensitivity to anti-PD1 therapy - Li, Hong-jiang; Yu, Zhi-yun; Gao, Hua-ping; Xu, Yi-ran; Li, Xue-yuan; Jiang, Wei; Chen, Di; Yan, Dong-ming; Yang, Chao; Liu, Xian-zhi (Frontiers in Oncology, 2025)
IntroductionGlioma, the primary cancerous tumor of the central nervous system in adults, has a poor outlook. Immune checkpoint blockade therapy has exhibited notable efficacy against various cancer types. Prior research has suggested that the adenosine A1 receptor (ADORA1) facilitates the proliferation of tumors in cancer. Nevertheless, the precise impact of ADORA1 on glioma progression and its influence on anti-programmed death receptor 1 (PD1) therapy, along with the underlying regulatory mechanisms, remain to be fully elucidated.MethodsBioinformatics was used to explore the correlation between ADORA1 expression and glioma prognosis. The effects of ADORA1 on glioma and anti-PD1 therapy were investigated in both laboratory settings and living organisms.ResultsThe results revealed a significant increase in ADORA1 expression in glioma, which was correlated with poor prognosis. Furthermore, ADORA1 inhibition facilitated glioma apoptosis by augmenting kininogen-1 (KNG1). ADORA1 inhibition enhanced T cell recruitment and increased glioma susceptibility to anti-PD1 therapy.DicussionOur findings indicate that inhibiting ADORA1 can induce apoptosis in glioma cells and increase their sensitivity to anti-PD1 therapy. ADORA1 may serve as a prognostic marker for glioma and a potential target to enhance the effectiveness of anti-PD-1 therapy.